2022-RA-1473-ESGO Randomized phase II CLIO study on olaparib monotherapy versus chemotherapy in recurrent ovarian cancer – results of the Leuven HRD test. (20th October 2022) - Loverix, Liselore; Vergote, Ignace; Vanderstichele, Adriaan; Busschaert, Pieter; Boeckx, Bram; Venken, Tom; van Nieuwenhuysen, Els; Baert, Thaïs; Han, Sileny; Neven, Patrick; Berteloot, Patrick; Olbrecht, Siel; et al.
Abstract : Introduction/Background: Poly(ADP-ribose)-polymerase inhibitors (PARPi) have changed the treatment landscape for high grade serous ovarian cancer. The CLIO trial (NCT02822157 ) evaluated olaparib (OLA) single-agent therapy versus physician's choice chemotherapy (CT) in recurrent epithelial ovarian cancer. Current available tests for homologous recombination deficiency (HRD) have been able to identify possible responders to PARPi, but improvements to these tests are necessary and validation in clinical trials is key. Methodology: With Leuven HRD test we provide an academic laboratory-developed method for HRD testing in ovarian cancer. The test was designed on DNA tumor samples of the biobank of University Hospitals Leuven and showed its predictive effect for OLA efficacy in the PAOLA-1/ENGOT-ov25 study (SGO 2022). Here we report the results of Leuven HRD test (LOH+TAI+LST) in the CLIO trial. Results will be compared to Myriad myChoiceDX on the same samples. Results: In CLIO 160 patients (60 PSOC and 100 PROC) were randomized 2:1 to OLA (n=107) or CT (n=53). Baseline characteristics were similar between both arms. Overall objective response rate (ORR) for OLA and CT were similar (24.3% and 28.3%, respectively). In PSOC, ORR was 35.0% and 65.0% for OLA and CT (p=0.053); in PROC, ORR was 17.9% and 6.1% for OLA and CT (p=0.134). All patients were tested for germline/somatic BRCA1/2 prior to inclusion. 117 FFPE tumor samples at diagnosis were retrieved and tested for HRD with Leuven HRD test. In PSOC Leuven HRD test was a good predictor of PFS benefit with HR0.35 (p=0.035). There was no difference in PFS in PROC based on Leuven HRD status (p=0.274). Myriad myChoiceDX testing on the same samples is ongoing and comparison of HRD test results will be presented at the meeting. Conclusion: Leuven HRD test is predictive for OLA efficacy not only in first-line setting but also in recurrent setting in the CLIO trial.